1993
DOI: 10.1101/sqb.1993.058.01.088
|View full text |Cite
|
Sign up to set email alerts
|

Probing Functional Organization within the Nucleus: Is Genome Structure Integrated with RNA Metabolism?

Abstract: The cell nucleus is remarkable in the complexity of critical functions it must perform, and yet this complexity contrasts sharply with the simplified view of the nuclear interior that has persisted for many years. The nucleus is involved in essentially all aspects of cell function and is directly responsible for such intricate tasks as genome packaging, DNA replication, differential gene transcription, RNA processing, selective RNA transport, and cell division. In recent years, great advances have been made in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 44 publications
5
55
0
Order By: Relevance
“…SC-35 domains. Interestingly, in B22 cells induced to undergo myogenesis by MyoD, the SC-35 domains became fewer but larger, as seen in several experiments (supporting earlier observations in differentiating rat muscle; Lawrence et al, 1993). Because infection did not result in MyoD expression in 100% of cells, it was important to identify myogeninexpressing cells by hybridizing to myogenin nuclear RNA, which showed that the level of association in these cells was 89% (Figure 3, C and D).…”
Section: Does Localization With Sc-35 Domains Correlate With Muscle Dmentioning
confidence: 60%
“…SC-35 domains. Interestingly, in B22 cells induced to undergo myogenesis by MyoD, the SC-35 domains became fewer but larger, as seen in several experiments (supporting earlier observations in differentiating rat muscle; Lawrence et al, 1993). Because infection did not result in MyoD expression in 100% of cells, it was important to identify myogeninexpressing cells by hybridizing to myogenin nuclear RNA, which showed that the level of association in these cells was 89% (Figure 3, C and D).…”
Section: Does Localization With Sc-35 Domains Correlate With Muscle Dmentioning
confidence: 60%
“…Subcellular compartmentalization of function is a common means by which the cell can regulate multiple processes that by necessity occur simultaneously (8,25,31,49,55). There are many examples of movement from one subcellular compartment to another as a means of regulating the activity of the shuttling protein.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of splicing factors are both widely distributed throughout the nucleus, excluding nucleoli, and are also concentrated in two distinct types of foci, referred to as ''speckles'' and coiled bodies (for review, see Lamond and Carmo-Fonseca 1993;Lawrence et al 1993;Spector 1993). Mammalian nuclei typically contain 20-50 speckles and 1-5 coiled bodies.…”
mentioning
confidence: 99%